Respuesta :
f ( 6 ) = -16·6²+32·6+90= -576 + 192 + 90 = -294
f ( 4 ) = -16· 4³+32·4+90=-256+128+90= -38
The average rate of change: [f(t2)-f(t1)]/ t2-t1=
[-294-(-38)] / (6-4) = -256 : 2 = -128 feet/s
f ( 4 ) = -16· 4³+32·4+90=-256+128+90= -38
The average rate of change: [f(t2)-f(t1)]/ t2-t1=
[-294-(-38)] / (6-4) = -256 : 2 = -128 feet/s
The value of the average rate of change of f(t) is -128feet/s.
We have given that,
f(t) = −16t^2 + 32t + 90
f ( 6 ) = -16·6²+32·6+90= -576 + 192 + 90
f ( 6 ) = -294
f ( 4 ) = -16· 4³+32·4+90=-256+128+90
f ( 4 )= -38
What is the formula for the average rate of change?
The average rate of change
[tex][f(t_2)-f(t_1)]/ t_2-t_1[/tex]
Therefore by using the formula we get,
=[-294-(-38)] / (6-4)
= -256 / 2
= -128 feet/s
Therefore the value of the average rate of change of f(t) is -128feet/s.
To learn more about the average rate visit:
https://brainly.com/question/24313700
#SPJ2